Housing market resilience: Neighbourhood and metropolitan factors explaining resilience before and after the US housing crisis. (October 2019) - Wang, Kyungsoon
The advent of the millennium witnessed unparalleled volatility in the housing market, a cycle of bust and recovery to which some US neighbourhoods were resilient and others not. Most planning scholars interested in resilience have paid little attention to examining the resilience of the housing market to economic shocks at the neighbourhood level across the USA. Using cluster analysis and hierarchical linear models, together with changes in housing prices, this study examines patterns and drivers explaining neighbourhood resilience within the context of metropolitan housing markets over periods of housing boom, bust, and recovery. Findings suggest that neighbourhood and metropolitan factors associated with housing market resilience varied across space and time: housing and mortgage market conditions affected neighbourhood recovery in the relatively short term while most urban form variables affected recovery over the long term. In addition, the associations and recovery patterns varied among the types of metropolitan areas, showing that neighbourhoods in strong markets had more drivers of resilience and reverted to their original status more quickly than those in weak markets, highlighting the growth of regional housing disparity during the housing recovery. Across the nation, however, home values in neighbourhoods that experienced more extreme periods of boom and bust underwent short-lived depreciation during the recession but long-term appreciation. This study should help policy makers establish sound policies that stabilise neighbourhoods and prevent future downturns.